Fiction on the fringe : novelistic writing in the post-classical age - Karla, Grammatiki A. (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2009)
A collection of essays that offers a comprehensive examination of texts that traditionally have been excluded from the main corpus of the ancient Greek novel and confined to the margins of the genre, such as the "Life of Aesop", the "Life of Alexander the Great", and the "Acts of the Christian Martyrs."